2019
DOI: 10.1021/acs.analchem.9b04198
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor 4 as a Novel Exosome Marker in MALDI-MS Analysis of Exosomes from Human Serum

Abstract: Exosomes are nanosized vesicles commonly found in biological fluids as a result of a secretion process involving endosomes and multivesicular bodies. The isolation and analysis of exosomes can be useful for noninvasive clinical diagnosis of a variety of human diseases. We investigated the utility of analyzing exosomal proteins, using matrix-assisted laser desorption/ionization combined with Fourier-transform ion cyclotron resonance mass spectrometry (MALDI-FTICR-MS), as a means of determining the presence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…One of the most prominent was properdin, which is an immune‐response‐linked protein. Interestingly, we also detected platelet factor 4 which has been recently identified as a novel exosome marker for human exosome serum (Nguyen et al, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…One of the most prominent was properdin, which is an immune‐response‐linked protein. Interestingly, we also detected platelet factor 4 which has been recently identified as a novel exosome marker for human exosome serum (Nguyen et al, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…These proteins are generally used as marker proteins for exosomes. Moreover, a recently study on the exosomes enriched from human serum identified with high confidence by MALDI-MS analysis the platelet factor 4 as a novel exosome marker that can be used as an alternative tool for confirming the exosome presence [ 149 ].…”
Section: Exosomes In Cardiovascular Diseasesmentioning
confidence: 99%
“…Several housekeeping genes or reference genes have been identified for different native tissues and body fluids, and stable endogenous RNAs have been proposed as internal controls; however, a consensus has not been reached [152] . In 2002, Vandesompele et al [153] demonstrated that the common RT-qPCR procedure of using only one control gene induced relatively large errors. In this study, they claimed that ideal single internal control genes do not exist and recommended the use of at least three adequate control genes for calculating a normalization factor [153] .…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…In 2002, Vandesompele et al [153] demonstrated that the common RT-qPCR procedure of using only one control gene induced relatively large errors. In this study, they claimed that ideal single internal control genes do not exist and recommended the use of at least three adequate control genes for calculating a normalization factor [153] . This issue with normalizers in gene expression analyses continues to this day, and the same issue is found with protein analyses.…”
Section: Challenges and Future Perspectivementioning
confidence: 99%